'Seek the welfare of the city where I place you into exile': towards a transformative strategy for the church's engagement with urban development - Cartwright, Simon J. (2012)
As a former urban development manager and now a minister in the Church of England, I offer this thesis as a theological reflection on the church’s engagement in the urban development process. By bringing together an understanding of urban policy with a hermeneutical reflection, a missional rationale is offered to the church in the context of urban change.